Pengembangan Aplikasi Deteksi dan Pencegahan Stunting Wilayah Kepulauan - Septy Nur Aini; Nazliansyah Nazliansyah; Okvita Ariyanti; Hafidz Ardiansyah (Universitas Malahayati Lampung, 2026)
ABSTRACT Stunting is a significant health problem in Indonesia. Although there has been a reduction in the stunting rate to 21.6% in 2022, this figure has not met the target of reducing stunting by 14% in 2024. Island regions have their own challenges in terms of disseminating information and health services related to stunting, so it is necessary to develop innovative technology-based solutions to detect and prevent stunting. This research aims to develop an Android-based stunting detection and prevention application model that can be used in island areas. This research uses a qualitative method with a Waterfall Design Thinking approach in application development. Data collection was carried out through observation, interviews and literature study with 30 respondents from the Belitung and East Belitung districts. Focus Group Discussion (FGD) was conducted to obtain input regarding application development. Application development using hardware instruments, software including Flutter software and Visual Studio Code.The research results show that the majority of respondents have used information technology such as social media, but only 3.3% have used Android-based applications specifically for stunting. All respondents had a positive perception of application use, with an emphasis on ease of use and accessibility. The FGD results also show that applications with offline features are really needed in areas with limited internet access. The